Chronological Trend of Climate in the Lumle Village Development Committee from Kaski District, Nepal - Timilsina, Yajna Prasad (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
A study has been conducted to examine how the temperature and precipitation in the Lumle Village Development of Kaski district, Nepal has varied over the thirty years period of 1997-2008. Maximum and minimum temperature and precipitation data were collected from Narayani basin. Maximum and minimum-summer and winter temperatures and precipitation categorized as pre-monsoon, monsoon and post-monsoon were studied with duration of 10 years separately and average annual temperature and precipitation trends of each decade was examined. The trends of temporal variations of temperature and precipitation were analyzed using secular trend of time series analysis with simple linear regression. For almost all decades maximum temperatures were found to be increasing trend whereas most of the minimum temperatures for three decades were found to be decreasing trend except for two events. So, maximum and minimum temperatures were seen increasing trend with average value 0.033 Celsius per year. Extreme temperature event was seen in 2000-2005. Post monsoon precipitation was seen erratic pattern with increasing during first decade and decreasing second and third decades. Pre-monsoon precipitation is constant pattern and trend of precipitation in the first two decades are increasing where as present decade seen decreasing. But average precipitation is increasing trend with rate of 2.5346mm/year because increasing trend of previous two decades outweighs present rate. Extreme drought period was seen in 2005. Actually, it is concluded that Lumle has decreasing trend in total seasonal precipitation and an increasing trend in temperatures. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 53-64